Study on Effect of Internet community in Socialization among Teenagers - et. al., Dr.Ranjitha M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Internet community can be a positive or negative influence among teenagers as most of the youth look upon the media as their best friend, owing to the influence of the society. The lack of attention from parents or inability to mingle with peers also forces children towards internet community. This study was conducted among teenagers to identify the upshot of internet community like Facebook, twitter, instagram and whatsapp. The study conducted among the age group 13-19 revealed that 70% of the participants use internet community through gadgets very often and this has affected their interaction with family members and friends. 90 percentage of the participants agreed that this has also affected their academic performance, participation in sports and extracurricular activities in a negative way. Children in Urban area are using social network for recreation whereas rural children are blindly addicted to this. At the same time, teenagers have not raised any concern related to health or poor eating habits due to addiction to social networks. The study was also a revelation that twenty first century teenagers are more cautious in terms of health and relationship. Due to the exposure gained in urban areas, participants are found to be very alert in trustworthiness of friends on internet community but participants from rural areas are found to give more importance and trustworthiness for their virtual friends which points out the necessity to educate rural students about the negative aspects of social websites.